Evaluation Of Role Of Oral Anti-Diabetic Drugs On Lipid Profile In Type 2 Diabetes Mellitus Patients - DR NAGENDRA KUMAR; DR KSHITISH KUMAR KSHITIZ; DR SURAJEET KUMAR PATRA (International Journal of Pharma and Bio Sciences, 2010)
Diabetes mellitus is a group of metabolic disorder characterized by chronic hyperglycemia and disturbances of carbohydrate, fat and protein metabolism associated with absolute or relative insulin deficiency. The present study was carried out to establish a correlationship between hyperglycemia of varying intensity with hyperlipidemia in NIDDM patients taking oral hypoglycemic drugs. The objective of the work was to find out whether hyperlipidemia was affected due to administration of a particular group of hypoglycemic drug. The total numbers of patients under study were 36 and control group consisted of 15 persons. All the 36 cases were divided according to age groups, sex, socio-economic status and dietary habits. Patients were divided into three groups i) patients taking Sulfonylurea ii) patients taking Biguanides and iii) patients taking Thiazolidinedione group of oral hypoglycemic. A morning blood sample after overnight fast was collected and serum total cholesterol, HDL and LDL cholesterol, triglycerides and plasma glucose were estimated. From the present study it is clear that Biguanides are more effective than Sulphonylureas in improving lipid profile in NIDDM cases. Also, the study suggests that NIDDM patients on oral hypoglycemic drugs are not susceptible to develop coronary artery disease.